Analysis Of A Compared Temperature Using Capillary Tube Different Measurement Length At Room 3 X 4 M2 Helping AC Portable - Rendy Wiseta; Riman Sipahutar; Muhammad Faizal (Universitas Sriwijaya, 2015)
At this time along with the times a lot of problems that occur in this world like the Earth's warming temperatures globally . Human needs of the air conditioning apparatus has become a staple in our daily lives . There is also a saying that the Air Conditioner ( AC ) has become a mandatory item installed in homes without air conditioning because of the environment around the home became more sultry and hot when we were in the neighborhood . In developments at this time have many types of AC marketed like Split AC , AC Windows , Central air conditioning and so on . A capillary tube expansion device or lowering pressure so cheap that researchers sought to examine the ratio of capillary -sized 33 , 54 , and 76 cm to the temperature of an air conditioner Portable. Results comparative study of the capillary tube length obtained the lowest total heat value is 9086 , 6925 Btu / Hr and the highest is 15144.4875 Btu / Hr .